Performance analysis of interlinking converter exchanging power between AC/DC renewable microgrids with advanced control technique - Seeramshetti, Mamatha; Gaddam, Mallesham (Institute of Advanced Engineering and Science, 2024)
In a distribution system there are many types of AC/DC microgrids integrated at different locations. These microgrids may contain conventional or renewable sources which generate power using natural resources. The power generated by these microgrid sources is uncertain as the natural resources are unpredictable. Therefore, powers from these AC/DC micro grids need to be shared so as to compensate the load demand throughout the distribution system. An interlinking converter (ILC) is connected between the AC/DC microgrids operated by a novel advanced PQ control technique. Both the DC and AC microgrids are interconnected through ILC achieving power exchange between them as per the power demand and generation on both microgrids. Different operating conditions are considered for the analysis and the simulation of these modules are done using MALTAB/Simulink software. Several parameters like DC link voltage, ILC currents, point of common coupling (PCC) frequency, total harmonic distortions (THDs) and active power values are considered for validating the stability of the considered system.